2022
DOI: 10.1186/s12934-022-01988-x
|View full text |Cite
|
Sign up to set email alerts
|

A purified and lyophilized Pseudomonas aeruginosa derived pyocyanin induces promising apoptotic and necrotic activities against MCF-7 human breast adenocarcinoma

Abstract: Background Pyocyanin, a specific extracellular secondary metabolite pigment produced by Pseudomonas aeruginosa, exhibits redox activity and has toxic effects on mammalian cells, making it a new and potent alternative for treating cancer. Breast cancer (BC) treatment is now defied by acquired and de novo resistance to chemotherapy, radiation, or targeted therapies. Therefore, the anticancer activity of purified and characterized pyocyanin was examined against BC in our study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…The laboratory extraction, purification, and characterization of PCN as well as cytotoxicity evaluation were discussed in our previous study [ 20 ]. In the present study, the sub-toxic concentrations of PCN (less than 45 µg/ml) were used for evaluation of the antibacterial, antibiofilm, and anti-QS activities of PCN against MRSA isolates.…”
Section: Methodsmentioning
confidence: 99%
“…The laboratory extraction, purification, and characterization of PCN as well as cytotoxicity evaluation were discussed in our previous study [ 20 ]. In the present study, the sub-toxic concentrations of PCN (less than 45 µg/ml) were used for evaluation of the antibacterial, antibiofilm, and anti-QS activities of PCN against MRSA isolates.…”
Section: Methodsmentioning
confidence: 99%
“…However, the authors concluded that the tested concentration of PYO in murine models (100 mg/ kg) was toxic and cannot be applied in therapy, rather than the dose of 750 µg/mL presented by Hamad et al (2020) that did not cause observable toxicity in tested rodents. PYO potential was also demonstrated in cancer research, where the viability of liver, pancreas, breast, lung, cervix, and skin cancer cell lines was reduced by this potential drug (Zhao et al 2014;Patil et al 2017;Moayedi et al 2018;Abdelaziz et al 2022). PYO may be used to produce other substances expressing anticancer properties.…”
Section: Why Is Pyocyanin Production Worth Controlling?mentioning
confidence: 98%
“…Company (Elbargisy 2021;Abdelaziz et al 2022). Furthermore, the optimal temperature of incubation differs among the strains, and the most used values are within the range of 28-37℃.…”
Section: How To Modulate Pyocyanin Production?mentioning
confidence: 99%
“…Pyocyanin, the signature metabolite of P. aeruginosa, is a blue-green, water-soluble phenazine pigment [114,115]. Phenazine compounds are commonly found in nature and are produced by bacteria such as Streptomyces and Pseudomonas.…”
Section: Pyocyaninmentioning
confidence: 99%
“…Specifically, pyocyanin disrupts the beating of human cilia and inhibits mammalian cell respiration thereby helping P. aeruginosa colonize the host lungs [122]. Pyocyanin is a zwitterion that crosses the host cell membrane and oxidizes NADH and NADPH molecules, generating reactive oxygen species (ROS) [115,123,124]. The ROS further contributes to cytotoxicity in the respiratory, vascular and central nervous systems of the eukaryotic hosts [125].…”
Section: Pyocyaninmentioning
confidence: 99%